The role of annexin A1 peptide in regulating PI3K/Akt signaling pathway to reduce lung injury after cardiopulmonary bypass in rats. (March 2023) - He, Yunzi; Zhang, Yuanjie; Wu, Hanhua; Luo, Junli; Cheng, Chi; Zhang, Hong
Introduction: Cardiopulmonary bypass (CPB) –induced lung ischemia-reperfusion (I/R) injury remains a large challenge in cardiac surgery; up to date, no effective treatment has been found. Annexin A1 (AnxA1) has an anti-inflammatory effect, and it has been proven to have a protective effect on CPB-induced lung injury. However, the specific mechanism of AnxA1 in CPB-induced lung injury is not well studied. Therefore, we established a CPB-induced lung injury model to explore the relevant mechanism of AnxA1 and try to find an effective treatment for lung protection. Methods: Male rats were randomized into five groups ( n = 6, each): sham (S group), I/R exposure (I/R group), I/R + dimethyl sulfoxide (D group), I/R + Ac2-26 (AnxA1 peptide) (A group), and I/R + LY294002 (a PI3K specific inhibitor) (AL group). Arterial blood gas analysis and calculation of the oxygenation index, and respiratory index were performed. The morphological changes in lung tissues were observed under light and electron microscopes. TNF-α and IL-6 and total protein in lung bronchoalveolar lavage fluid were detected via enzyme-linked immunosorbent assay. The expressions of PI3K, Akt, and NF-κB (p65) as well as p-PI3K, p-Akt, p-NF-κB (p65), and AnxA1 were detected via western blotting. Results: Compared with the I/R group, the A group showed the following: lower lung pathological damage score; decreased expression of IL-6 and total protein in the bronchoalveolar lavage fluid, and TNF-α in the lung; increased lung oxygenation index; and improved lung function. These imply the protective role of Ac2-26, and show that LY294002 inhibited the ameliorative preconditioning effect of Ac2-26. Conclusion: This finding suggested that the AnxA1 peptide Ac2-26 decreased the inflammation reaction and CPB-induced lung injury in rats, the lung protective effects of AnxA1may be correlated with the activation of PI3K/Akt signaling pathway.